Universities and smart specialisation in less developed European regions: an evidence-based overview - Wibisono, Eristian (European Spatial Research and Policy, 2022)
This paper aims to review the evidence demonstrating the role of universities in the knowledge diffusion function for Smart Specialisation strategies. It is not new if many experts question whether Smart Specialisation will apply equally in all regions, plus the reason that the study of the role of universities in Smart Specialisation still needs much attention. Through this evidence-based literature review, I have identified three main points that support the role of universities for Smart Specialisation in less developed regions of Europe, including resources in regional innovation systems, public sector investment support for RandD, and strong bonds of the Triple Helix actors.